Comparison of the coronal sealing qualities of three temporary filling materials - Lam, Michael Chia Sua
Comparisons were made on the coronal sealing quality of three temporary filling materials. Access cavities filled with Cavit, zinc oxide-eugenol cement and Fermin were tested for leakage with methylene blue at room temperature and leakage when subjected to 60ºC and 4ºC.